Role Of Complex Nutrients, Vitamins And Amino Acids On Biosorption Of Hg++ BY Hg++ Resistant - KHUSHI MUKHERJEE,; AJIT KUMAR BANIK, (International Journal of Pharma and Bio Sciences, 2011)
Remediation of Hg++ contaminated wastewater can be accomplished by Hg++ resistant Saccharomyces cerevisiaeA100. The physico-chemical mode of biosorption process is largely dependent on the charge bearing cell surface ligands. Optimum cell growth and multiplication provides the exposure of adequate amount of charged ligands on the cell surface that ultimately facilitate greater rate of biosorption of Hg++. Hence, The growth promoting factors like vitamins , amino acids indirectly play a significant role in biosorption process. Thiamine-HCl (2.0µg/ml) and biotin (1.0µg/ml) increases the biosorption upto 95.67% and 96.78% respectively. L(-)Tryptophan (0.75mg/ml) promotes the biosorption upto 90.24%. Complex nutrients are the cheap sources of vitamins, amino acids, metals in trace amounts etc. Among 10 different tested complex nutrients, meat extract and soya been meal show some positive effect where as peptone and rice bran extract significantly declines the biosorption potential of the used biomass.